Are prehospital airway management resources compatible with difficult airway algorithms? A nationwide cross-sectional study of helicopter emergency medical services in Japan - Ono, Yuko; Shinohara, Kazuaki; Goto, Aya; Yano, Tetsuhiro; Sato, Lubna; Miyazaki, Hiroyuki; Shimada, Jiro; Tase, Choichiro (Journal of anesthesia, 2016)
Purpose Immediate access to the equipment required for difficult airway management (DAM) is vital. However, in Japan, data are scarce regarding the availability of DAM resources in prehospital settings. The purpose of this study was to determine whether Japanese helicopter emergency medical services (HEMS) are adequately equipped to comply with the DAM algorithms of Japanese and American professional anesthesiology societies. Methods This nationwide cross-sectional study was conducted in May 2015. Base hospitals of HEMS were mailed a questionnaire about their airway management equipment and back-up personnel. Outcome measures were (1) call for help, (2) supraglottic airway device (SGA) insertion, (3) verification of tube placement using capnometry, and (4) the establishment of surgical airways, all of which have been endorsed in various airway management guidelines. The criteria defining feasibility were the availability of (1) more than one physician, (2) SGA, (3) capnometry, and (4) a surgical airway device in the prehospital setting. Results Of the 45 HEMS base hospitals questioned, 42 (93.3 %) returned completed questionnaires. A surgical airway was practicable by all HEMS. However, in the prehospital setting, back-up assistance was available in 14.3 %, SGA in 16.7 %, and capnometry in 66.7 %. No HEMS was capable of all four steps. Conclusion In Japan, compliance with standard airway management algorithms in prehospital settings remains difficult because of the limited availability of alternative ventilation equipment and back-up personnel. Prehospital health care providers need to consider the risks and benefits of performing endotracheal intubation in environments not conducive to the success of this procedure.